Da'wah as a Commodity: Analysis of Commodification and Mediatization of Religion in the Religious Talk Show Program of Wisata Hati and Islam Itu Indah - Hikmatussahri Ramadan; Ikbal Nursamsi; Asep Iwan Setiawan (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
In this modern era, da'wah is often exploited for material gain. Da'wah activities should be used to disseminate Islamic values ​​to its adherents, as the saying